Management of refractory heartburn: are we convinced that surgery is better than medical treatment? - Md Jalil, Muhammad Ateeq; Wong, Zhiqin; Raja Ali, Raja Affendi; Lee, Yeong Yeh (Royal College of Physicians of Edinburgh, 2020)
In a nutshell, this was a single centre, randomised-controlled trial comparing surgical vs medical modality in treating protonpump inhibitor (PPI)-refractory heartburn; a common condition where optimal treatment approach is not known. All patients referred to the Veterans Affairs gastroenterology clinics for refractory heartburn were screened. Eligible patients would complete the gastro-oesophageal refl ux disease (GORD) – Health Related Quality of Life (GORD-HRQL) questionnaire followed by 2-week trial of omeprazole at a dose of 20 mg twice daily, after which the GORD-HRQL was repeated. Patients who did not show improvement (i.e. decrease of >50% in the initial GORD-HRQL score) then underwent endoscopy with biopsies from the lower oesophagus, but also oesophageal manometry and intraluminal impedance– pH monitoring while continuing omeprazole at the same dose and frequency. Patients with severe refl ux oesophagitis, nonGORD endoscopic abnormalities, oeosinophilic oesophagitis, achalasia or absent contractility were excluded. Other patientreported outcomes included depression, anxiety and health function.